Rewarding Commitment to Attend School: A Field Study with Indigenous Australian High School Students - Azhar Hussain Potia; Juliana Silva-Goncalves; Benno Torgler; Uwe Dulleck (Center for Economic Studies and ifo Institute (CESifo), 2019)
We introduce a novel incentive program aimed at decreasing school absenteeism based on the effect of voluntary promises in motivating desirable behaviour. In contrast to a standard program, in which students receive a reward conditional on having achieved a school attendance rate of at least 90 percent, in the promise program, they receive the reward up front, conditional on their commitment to invest their best efforts to reach the attendance target. We assess the effectiveness of the promise program through a field study involving Indigenous Australian high school students, a population who tends to have lower education achievement and socioeconomic advantage than their non-Indigenous counterparts. We find that the promise program significantly decreased unexplained absences compared to the standard program but that it did not influence overall school absences. Our findings suggest that voluntary promises coupled with small gifts are effective in influencing behaviour of disadvantaged students. At the same time, we need further research on how to best design such programs to achieve positive effects in reducing school absenteeism.
Keywords: I24; I25; I28; 330; school absenteeism; promises; upfront rewards; Aboriginal and Torres Strait Islander students